2019
DOI: 10.1016/j.cell.2019.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Intestinal Carbohydrate Metabolism Promote Food Intake and Sperm Maturation

Abstract: Highlights d Intestinal carbohydrate metabolism is male-biased and region-specific d Testes masculinize gut sugar handling by promoting enterocyte JAK-STAT signaling d The male intestine secretes citrate to the adjacent testes d Gut-derived citrate promotes food intake and sperm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(137 citation statements)
references
References 167 publications
(205 reference statements)
8
129
0
Order By: Relevance
“…In turn, the gut receives multiple signals emanating from the fat body, brain and gonads to adjust digestion, metabolism and gut motility (blue lines). AKH, adipokinetic hormone; AKHR, AKH receptor; Daw, dawdle; DH44, diuretic hormone 44; DILPs, Drosophila insulin-like peptides; Upds, unpaired ligands spermatogenesis by increasing circulating citrate levels, demonstrating a role in the gonad-intestine axis in coupling diet and sperm production (Hudry et al, 2019). During pathogenic infections reallocation of energy takes place to support the energy expensive task of mounting an immune response.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…In turn, the gut receives multiple signals emanating from the fat body, brain and gonads to adjust digestion, metabolism and gut motility (blue lines). AKH, adipokinetic hormone; AKHR, AKH receptor; Daw, dawdle; DH44, diuretic hormone 44; DILPs, Drosophila insulin-like peptides; Upds, unpaired ligands spermatogenesis by increasing circulating citrate levels, demonstrating a role in the gonad-intestine axis in coupling diet and sperm production (Hudry et al, 2019). During pathogenic infections reallocation of energy takes place to support the energy expensive task of mounting an immune response.…”
Section: F I G U R Ementioning
confidence: 99%
“…The gut is well-positioned to sense fluctuation in the external environment, and it communicates extensively with other organs to allow a coordinated physiological response across tissues. One example is nutrient availability and/or quality, which is sensed by the gut and relayed to other organs to adjust metabolism, energy balance, and feeding behavior (Alfa et al, 2015;Hudry et al, 2019;Scopelliti et al, 2019;Song et al, 2017;Song, Veenstra, & Perrimon, 2014). Reversely, the gut receives nutrient information from the fat body, another important nutrient-sensing organ, and responds by adjusting ingestion, digestion, and absorption of nutrients according to nutrient abundance (Chng, Sleiman, Schupfer, & Lemaitre, 2014;Dus et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4a). To detect relative differences in lactate levels in loser and winner cells, we used a genetically encoded lactate reporter (UAS-lactate FRET) 23 , which we expressed throughout the entire tissue (nub-Gal4, UASlactate FRET). Clonal analysis was conducted via the LexA/lexO binary system 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Imaging experiments were performed using dissected imaginal wing discs. A genetically encoded lactate reporter (UAS-lactate FRET) 23 , was co-expressed within clones expressing gene-of-interest (goi) or UAS-lacZ-RNAi. Alternatively, the sensor was expressed tissue wide, under the control of nubbin (nub-Gal4 > UAS-lactate FRET).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Drosophila have led to a deep understanding of how sex chromosome number is interpreted to activate downstream pathways controlling morphological and behavioral differences between male and female flies. A recent study by Hudry et al (2019) comparing gene expression in the guts of males and females revealed male-biased expression of enzymes involved in carbohydrate transport and utilization. Hudry et al demonstrate that, surprisingly, this sex difference in gut gene expression is controlled by the adjacent male gonad, which produces the ligand Upd1.…”
Section: Organ Cross-talk and Sex Differences In Physiologymentioning
confidence: 99%